Identifying perinatal depression and anxiety : evidence-based practice in screening, psychosocial assessment and management - Milgrom, Jeannette; Gemmill, Alan W. (Chichester, UK ; Malden, MA : John Wiley & Sons Inc., 2015)
'Identifying Perinatal Depression and Anxiety brings together the very latest research and clinical practice on this topic from around the world in one valuable resource. Examines current screening and management models, particularly those in Australia, England and Wales, Scotland, and the United States. Discusses the evidence, accuracy, and limitations of screening methods in the context of challenges, policy issues, and questions that require further research. Up to date practical guidance of how to screen, assess, diagnose and manage is provided. Considers the importance of screening processes that involve infants and fathers, additional training for health professionals, pathways to care following screening, and the economics of screening. Offers forward-thinking synthesis and analysis of the current state of the field by leading international experts, with the goal of sketching out areas in need of future research'--Provided by publisher.
How to Score and Interpret EPDS ResultsHow to Interpret the Anxiety Subscale; How to Explain Screening Results to Women; How to Respond to Question 10: Risk Assessment; Developing a management plan; Conclusions; References; Chapter 5 Screening Tools and Methods of Identifying Perinatal Depression; Introduction; EPDS; Generic Self-Report Instruments; Other Perinatal-Specific Self-Report Instruments; Pregnancy Risk Assessment Monitoring System; PDSS; Bromley Postnatal Depression Scale; The Pitt Depression Scale; Clinician-Rated Scales; Case-Finding Perinatal Depression; Case-finding questions.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Postpartum depression -- Diagnosis; Mental illness in pregnancy; Anxiety Disorders -- diagnosis; Depression, Postpartum -- diagnosis; Anxiety Disorders -- diagnosis; Anxiety Disorders -- psychology; Depression, Postpartum -- psychology; Evidence-Based Medicine -- methods; Internationality; Anxiety disorders -- Diagnosis; Anxiety disorders -- Psychology; Depression, Postpartum -- Diagnosis; Depression, Postpartum -- Psychology; Electronic books